The Attitudes Towards the Cultural Globalization and The Atheism - A Field Study on Palestinian University Students - Khalili, Fakher Nabeel (Journal of Educational and Psychological Sciences, 2020)
The study aimed to investigate the Palestinian universities students’ attitudes towards the cultural globalization and the atheism in the West Bank. The study also examined the effects of gender, educational level, and age and it tested the relationship between attitudes towards the cultural globalization and the atheism. A sample of 345 Palestinian universities students was selected. An electronic questionnaire was designed to collect data. The construct validity and reliability analysis by Chronbach Alpha were used. The attitudes towards the cultural globalization scale consisted of (17) items and all items correlated significantly with the total score with Cronbach Alpha of (0.84). The attitudes towards atheism scale consisted of (40) items and all items correlated significantly with the total score with Cronbach Alpha of (0.92). The results showed that the attitudes of the Palestinian universities students towards atheism were negative with mean of 1.87 , and the percentage of the positive attitudes towards atheism was (37%). The attitudes towards cultural globalization, ranged between rejection and acceptance. The mean was 2.92, and the percentage of the positive attitudes towards cultural globalization was (58%). The percentage of unbeliever students (atheist, deist, and agnostic) was (15%). Moreover, the results showed that the variables of gender, educational level, and age did not affect the attitudes towards cultural globalization and atheism. There was a positive significant relationship between attitudes towards atheism and cultural globalization (r= 0.44, α <0.01). The study recommended to be careful and aware of the elements of cultural globalization, and choose what suits the local and Arab context.